2022
DOI: 10.3389/fpsyg.2022.1029503
|View full text |Cite
|
Sign up to set email alerts
|

The influence of androgynous streamers on consumers’ product preferences

Abstract: Since the rapid development of network technology, the rise of live-streaming shopping platforms has followed. Some streamers influence consumers’ preferences for products through their gender role attributes, thus generating great commercial value. Based on attachment theory and using an experimental approach, this study explored the impact of streamers’ gender roles (single gender/androgyny) on consumers’ preferences through 2 studies. Study 1 shows the androgynous streamer elicits a higher product preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The reason is that the higher the traditional gender ideology, the higher the level of gender schematization of a consumer, the more rigid the impression of gender roles, the more inclined to process the advertisement information through the perspective of gender, and therefore has a higher preference for gender role endorsement ( Wang and Lianrong, 2005 ). Empirical studies on live e-commerce have also found that consumers with higher levels of gender ideology pay more attention to messages that are consistent with gender stereotypes ( Wenting et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason is that the higher the traditional gender ideology, the higher the level of gender schematization of a consumer, the more rigid the impression of gender roles, the more inclined to process the advertisement information through the perspective of gender, and therefore has a higher preference for gender role endorsement ( Wang and Lianrong, 2005 ). Empirical studies on live e-commerce have also found that consumers with higher levels of gender ideology pay more attention to messages that are consistent with gender stereotypes ( Wenting et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the mutual penetration of male and female occupations, the boundaries between male and female gender roles are becoming increasingly blurred. Traditional gender stereotypes are merging, and androgyny has become a trend ( Wenting et al, 2022 ). The proposal of androgyny means that individuals can freely manifest both male and female characteristics without following traditional gender stereotypes ( Bem, 1974 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations